Anal Incontinence Clinical Management and Surgical Techniques - Docimo, Ludovico; Brusciano, Luigi (Updates in Surgery, 2023)
This open access book describes the latest advances in the anal incontinence diagnostic and therapeutic processes. Anal incontinence is a devastating condition heavily impacting on the patients' lives. Those suffering from this disorder are generally very embarrassed and reluctant to undergo an appropriate clinical evaluation, thus becoming more isolated and worsening the quality of their life. Luckily, nowadays a wide range of treatments is available to improve this oppressive condition; however, the recognition of the related pathophysiological alterations is mandatory to grant its successful management. This volume will help the surgeons community to keep abreast of developments in diagnostics and treatment of this impairing condition. and will provide all health professionals with the appropriate tools to face this impairing condition.